Photochromic behavior and mechanism of indole thiosemicarbazide derivates in amorphous powder, solution and nanofiber. (October 2019) - Che, Yuanyuan; Liu, Lang; Zhao, Jianzhang; Yu, Yuming; Zhao, Xianmei
Abstract: A series of Schiff bases containing the indole group were synthesized. The compound 2-[(1-methyl-1H-indol-3-yl)methylene] hydrazinecarbothioamide (4 ) exhibits excellent reversible photochromic properties both in solid−solid state and solution. Moreover, the nanofiber containing the compound 4 also shows excellent photochromic properties, which are better than the amorphous powder of 4 itself. Based on the experiment results and theoretical calculation, we confirm that the photochromic properties originate from the intermolecular proton transfer, resulting in the isomerization of the thioketone−form and the thioalcohol−form in the hydrazinecarbothioamide. This unique photochromic system is obviously different from that of traditional Schiff bases, such as salicylideneanilines. Graphical abstract: A series of Schiff bases containing indole group were synthesized. Some of which exhibit reversible photochromic properties in solid state. Moreover, the composited nanofibers show faster photochromic rate and better fatigue resistant than in powder form. Their photochromic properties originate from the intermolecular proton transfer, resulting in the isomerization between the thioketone−form and the thioalcohol−form of the molecules, which is obvious different from that of classic Schiff bases such as salicylal anils. Image 1 Highlights: A series of Schiff bases containing indole group, which is different from classic Schiff bases, have been synthesized. Compound 2-[(1-methyl-1H-indol-3-yl)methylene] hydrazinecarbothioamide exhibits reversible photochromic properties. The composited nanofibers show excellent photochromic property than its amorphous powder form. The photochromic mechanism is ascribed to the isomerization between the thioketone-form and the thioalcohol-form.